Effects of cleaning methods upon preservation of stable isotopes and trace elements in shells of Cyprideis torosa (Crustacea, Ostracoda): implications for palaeoenvironmental reconstruction - Roberts, L.R.; Holmes, J.A.; Leng, Melanie J.; Sloane, H.J.; Horne, D.J. (Elsevier, 2018)
The trace element (Sr/Ca and Mg/Ca) and stable isotope (δ¹⁸O and δ¹³C) geochemistry of fossil ostracod valves provide valuable information, particularly in lacustrine settings, on palaeo-water composition and palaeotemperature. The removal of sedimentary and organic contamination prior to geochemical analysis is essential to avoid bias of the results. Previous stable isotope and trace element work on ostracod shells has, however, employed different treatments for the removal of contamination beyond simple ‘manual’ cleaning using a paint brush and methanol under a low-power binocular microscope. For isotopic work pre-treatments include chemical oxidation, vacuum roasting and plasma ashing, and for trace element work sonication, chemical oxidation and reductive cleaning. The impact of different treatments on the geochemical composition of the valve calcite has not been evaluated in full, and a universal protocol has not been established. Here, a systematic investigation of the cleaning methods is undertaken using specimens of the ubiquitous euryhaline species, Cyprideis torosa. Cleaning methods are evaluated by undertaking paired analyses on a single carapace (comprising two valves); in modern ostracods, whose valves are assumed to be unaltered, the two valves should have identical geochemical and isotopic composition. Hence, when one valve is subjected to the chosen treatment and the other to simple manual cleaning any difference in composition can confidently be assigned to the treatment method. We show that certain cleaning methods have the potential to cause alteration to the geochemical signal, particularly Mg/Ca and δ¹⁸O, and hence have implications for palaeoenvironmental reconstructions. For trace element determinations we recommend cleaning by sonication and for stable isotope analysis, oxidation by hydrogen peroxide. These methods remove contamination, yet do not significantly alter the geochemical signal.